1976
DOI: 10.1079/bjn19760099
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional evaluation of the protein of dried tomato pomace in the rat

Abstract: I . Nutritional evaluation of dried tomato pomace (DTP-20) as a source of protein was carried out using weanling rats. Comparisons were made with casein (CS), soya-bean meal (SOM-45) and the hydrocarbon-grown yeast Toprina (BP-T). The growth-promoting effects of the diets were evaluated over a period of 28 d of ad lib. feeding. 3.The reason for the decrease in growth and the reduced PER and NPU values recorded for the methionine-supplemented group of rats is not clear and it is discussed in connexion with an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

1980
1980
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 10 publications
(5 reference statements)
0
5
0
1
Order By: Relevance
“…than that of cereal grain derived proteins but lower than al., 1984) including potato waste meal and oat groats those of casein (Drouliscos, 1976) and whole-egg protein (FAO/WHO, 1965). Similar results were obtained from the essential amino acid indices and protein scores (data not shown) calculated from their amino acid composition (Table V) by the methods of Block and Mitchell (1946) and Oser (1951).…”
Section: Resultsmentioning
confidence: 99%
“…than that of cereal grain derived proteins but lower than al., 1984) including potato waste meal and oat groats those of casein (Drouliscos, 1976) and whole-egg protein (FAO/WHO, 1965). Similar results were obtained from the essential amino acid indices and protein scores (data not shown) calculated from their amino acid composition (Table V) by the methods of Block and Mitchell (1946) and Oser (1951).…”
Section: Resultsmentioning
confidence: 99%
“…Tomato pomace replaced increased amounts of soybean meal in the experimental diets and rumen degradability of TP has been reported to be lower than that of soybean meal [2], which would indicate greater bypass protein in TP than in soybean meal. According to Drouliscos [44], the essential amino acids profile in TP protein is similar to that in soybean meal, but the low values of IDCP observed in our study indicate that about half of the protein reaching the small intestine may not be digested, whereas intestinal digestibility of soybean meal is greater than 90% [43]. In agreement with these results, Fondevila et al [2] and Yuangklang et al [40] reported a significant decrease in CP digestibility when replacing soybean meal by TP in the diet of lambs and beef cattle, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The potential of tomato seeds as a food source has been reported (Ammerman et al, 1963;Drouliskos, 1976;Kramer and Kwee, 1977a,b;Abdel-Rahman, 1982;Al-Wandawi et al, 1985;Lasztity et al, 1986;Rahma et al, 1986). The approximate composition of tomato seeds (dry basis) is: fat 1 l-20%, protein 15-22% and ash 3-7%.…”
Section: Introductionmentioning
confidence: 93%